English observed - MacAndrew, Richard (Thomson Heinle, 2002)
This teacher's handbook on language awareness aims to make teachers more aware of natural English. By observing modern English where the speaker/writer seems to "break the rules", this book challenges the model of standard English and the idea of correctness in the EFL classroom